2016
DOI: 10.2151/sola.2016-004
|View full text |Cite
|
Sign up to set email alerts
|

Active Role of the ITCZ and WES Feedback in Hampering the Growth of the Expected Full-Fledged El Niño in 2014

Abstract: We investigated features of the atmosphere and ocean to seek a possible candidate that suppressed the growth of the El Niño event in 2014. In the boreal summer-fall season, equatorially antisymmetric sea surface temperature (SST) anomalies with a positive (negative) sign to the north (south) of the equator prevailed in the central and eastern tropical Pacific. In association with the SST anomalies, cumulus convective activity was enhanced in the region of the climatological Intertropical Convergence Zone (ITCZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Although the weakening of easterly trade wind and the North Pacific high are known as typical response to El Niño event, El Niño conditions were quite weak until the early 2015 and effect of El Niño event on atmospheric circulation fields were also unobvi- ous (Menkes et al 2014;Maeda et al 2016). Therefore, the results presented here suggest that some processes other than ENSO at mid-and/or high latitudes played important roles for the warming in the North Pacific in 2013/14/15.…”
Section: Gasst Variability and Contribution Of The Basinaveraged Sstsmentioning
confidence: 58%
See 1 more Smart Citation
“…Although the weakening of easterly trade wind and the North Pacific high are known as typical response to El Niño event, El Niño conditions were quite weak until the early 2015 and effect of El Niño event on atmospheric circulation fields were also unobvi- ous (Menkes et al 2014;Maeda et al 2016). Therefore, the results presented here suggest that some processes other than ENSO at mid-and/or high latitudes played important roles for the warming in the North Pacific in 2013/14/15.…”
Section: Gasst Variability and Contribution Of The Basinaveraged Sstsmentioning
confidence: 58%
“…In addition, there are meridionally antisymmetric patterns with positive (negative) SLP anomalies in the Northern (Southern) hemisphere around the eastern part of the tropical Pacific. Maeda et al (2016) suggest that feedbacks among wind, evaporation, and SST and intensified convective activity in the intertropical convergence zone contributed to antisymmetric patterns associated with warming in the eastern tropical region in the North Pacific. As a whole, weaker wind anomalies suppress evaporation, and latent heat loss from the ocean is reduced around the extratropics and in the central to eastern tropical region of the North Pacific (Fig.…”
Section: Gasst Variability and Contribution Of The Basinaveraged Sstsmentioning
confidence: 95%
“…We also analyzed the output of the numerical experiment using a linear baroclinic model (LBM). The experimental design was documented by Maeda et al (2016).…”
Section: Datamentioning
confidence: 99%
“…Meanwhile, equatorially antisymmetric SSTAs with positive (negative) anomalies north (south) of the equator prevailed in the central and eastern tropical Pacific during the summer-fall 2014. Maeda et al (2016) suggested that the intensified evaporative cooling of SST as a result of the prevailing southerly surface wind across the equator contributed to the suppression of the El Niño growth in 2014. They insisted that the wind-evaporation-SST (WES) feedback (Xie and Philander 1994) is the physical background of the surface southerlies in the near-equatorial region and the equatorially antisymmetric SSTAs.…”
Section: Introductionmentioning
confidence: 99%
“…This could explain the recent trend in the suppression of warming in the eastern Pacific including the aborted El Niño of 25 2014 (Maeda et al, 2016;Wu et al, 2017) and a decrease in the occurrence of east Pacific-type El Niños. It should also be noted that the El Niño of 2015/16 was one of the largest events; however, it was a mixed type with smaller warming in the eastern Pacific (Paek et al, 2017), as can also be seen in the OLR field in Fig.…”
mentioning
confidence: 95%